The Relationship Between Psychological Functioning in a College Sample and Retrospective Reports of Parental Loyalty Conflicts and Psychological Maltreatment. Issue 2 (17th February 2019) - Wozencraft, Theresa A.; Tauzin, Monica; Romero, Lori
ABSTRACT: Two-hundred forty participants completed questionnaires that explored parental unions, experiences of parental loyalty conflict behaviors, psychological functioning, and frequency of exposure to maltreatment. Significant relationships were found between nonintact parental union status and experiences of parental loyalty conflict, parental loyalty conflict and psychological abuse, and parental loyalty conflict and anxiety and depression symptoms. Relatively low frequencies of experiencing parental loyalty conflict can negatively affect psychological functioning. Implications for psychological, social, and legal service providers are presented.